Examine the Comparison of Efficacy Between Intracameral and Sub Conjuctival Dexamethasone for the Prevention of Postoperative Inflammation in Patients with Cataract Surgery - Mohammad Aamir Khan, Fawad Ahmad, Muhammad Ahsen, Faisal Anwar, Muhammad Aamir Shahzad, Shahid Anwar Bhatti, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The main purpose of this study is to evaluate the efficacy of intracameral and subconjunctival injections of dexamethasone in the prevention of postoperative inflammation in patients who are having cataract surgery. Study Design:Observational/comparative study Place and Duration: Conducted at Jinah International Hospital , Abbottabad, from February 2021 to August 2021. Methods: Total 90 patients of both sexes with ages 3-15 years were presented in this study. All the included patients underwent cataract surgery. After obtaining the permission from parents, we collected demographic data on all of the enrolled children, including their age, gender, and place of residence. 45 patients received intracameral in group A and sub-conjunctival dexamethasone provided to 45 patients of group B. Post-operatively slit lamp biomicroscopy was done to assess inflammation after 1st and 3rd day between both groups. SPSS 22.0 was used to analyze all data. Results: Among 90 patients, majority of the cases were males 57 (63.3%) and rest were females 33 (36.7%). The mean age of the patients in group A was 9.6±14.76 years and in group B mean age was 8.6± 8.52 years.25 (55.6%) patients in group A and 22 (48.9%) cases of group B had urban residency. Post-operative, we found higher frequency of inflammation in group B in 12 (26.7%) as compared to group A in 3 (6.7%) cases with p value <0.05. Conclusion:In children having cataract surgery, we came to the conclusion that an intracameral injection of dexamethasone is more successful than a sub-conjunctival injection of dexamethasone at preventing postoperative inflammation.